2022
DOI: 10.1039/d2tb01263d
|View full text |Cite
|
Sign up to set email alerts
|

The role of nanopores constructed on the micropitted titanium surface in the immune responses of macrophages and the potential mechanisms

Abstract: Delayed transition of pro-inflammatory M1 to pro-healing M2 of macrophages (MΦs) on implant surface is one of the most important reasons accounting for poor osseointegration. The present work proposes to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Furthermore, Ce-TA enhances bone integration of intra-osseous implants in diabetic rats (He et al, 2021). Consistent with the perspective of immunology, Hang et al (2022) Reagents capable of mitochondrial oxidative suppression, such as adiponectin, ipriflavone and resveratrol (Corrêa et al, 2021;Hua et al, 2020;Tao, Zhou et al, 2020), can improve osseointegration in different animal models. Adiponectin, a fat-derived adipokine with anti-diabetic efficacy, can reverse ROS overproduction and alleviate mitochondrial damage by activating AMPK, thus reversing osteoblast impairment and improving the osteointegration (Hu et al, 2017).…”
Section: Mitochondrial Therapeutic Strategies For Improving Implant I...mentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, Ce-TA enhances bone integration of intra-osseous implants in diabetic rats (He et al, 2021). Consistent with the perspective of immunology, Hang et al (2022) Reagents capable of mitochondrial oxidative suppression, such as adiponectin, ipriflavone and resveratrol (Corrêa et al, 2021;Hua et al, 2020;Tao, Zhou et al, 2020), can improve osseointegration in different animal models. Adiponectin, a fat-derived adipokine with anti-diabetic efficacy, can reverse ROS overproduction and alleviate mitochondrial damage by activating AMPK, thus reversing osteoblast impairment and improving the osteointegration (Hu et al, 2017).…”
Section: Mitochondrial Therapeutic Strategies For Improving Implant I...mentioning
confidence: 67%
“…Consistent with the perspective of immunology, Hang et al. ( 2022 ) constructed nanopores on the micro‐pitted Ti surface to promote switching of macrophages from M1 to the M2 form to improve osseointegration by reducing mROS. These findings open a new window for the design of implant surfaces from the perspective of mitochondrial oxidative modulation.…”
Section: Mitochondrial Therapeutic Strategies For Improving Implant I...mentioning
confidence: 92%
“…With the development of society, the demand for high-performance energy materials is increasing. Owing to the wide application in photoelectrocatalysis, biosensors, supercapacitors, and so on, the preparation of TiO 2 has been a research hot spot for a long time. , Owing to the optical, structured, and electronic advantages, nanostructured TiO 2 -based photoelectrodes are promising for application as photoelectrochemical (PEC) devices, and photoelectrodes based on nanowire, nanorod, and nanoparticle structure have been widely studied. Nowadays, many researchers focus on the catalysts, such as TiO 2 /Ti 3 C 2 , Bi/BiOBr, and N-graphyne/BiOCl 0.5 Br 0.5 , but a few focus on its carrier. However, the photoelectrochemical properties of anodic TiO 2 nanotubes (ATNTs), one of its important carriers, have been studied less. It is worth mentioning that the ATNT array is usually formed in the electrolyte containing halogen ions typically, whereas the dense film in the electrolyte without halogen ions. Some researchers attributed the formation of porous film to an electrochemical dissolution reaction (i.e., TiO 2 + 6F – + 4H + → [TiF 6 ] 2– + 2H 2 O), and some other researchers suggested that the mechanism of porous film formation is related to the contamination layer formed by halogen ions. In summary, all of these studies supported the conclusion that the anion is indispensable for the formation of anodic TiO 2 nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Nonnoble metal-based catalysts have low cost and adjustable electronic structures, 10,11 mainly including alloys, 12–14 oxides, 15–17 phosphides, 18–20 sulfides, 21,22 nitrides, 23 LDH, 24–27 MOFs, 28–30 and composite materials of transition metals ( e.g. , manganese, cobalt, nickel, iron, copper, and molybdenum).…”
Section: Introductionmentioning
confidence: 99%
“…Nonnoble metal-based catalysts have low cost and adjustable electronic structures, 10,11 mainly including alloys, [12][13][14] oxides, [15][16][17] phosphides, [18][19][20] sulfides, 21,22 nitrides, 23 LDH, [24][25][26][27] MOFs, [28][29][30] and composite materials of transition metals (e.g., manganese, cobalt, nickel, iron, copper, and molybdenum). 31,32 Among them, LDHs have become one of the most advanced OER catalysts owing to their adjustable composition and structure.…”
Section: Introductionmentioning
confidence: 99%